Razvoj srca - Zorc, Marjeta (Medicinski razgledi, 2003)
The cardiovascular system is the first major organ system that develops and starts functioning in a growing embryo, because diffusion alone can no longer supply it with enough oxygen and nutrients. The heart forms at the end of the third week from the splanchnic mesoderm as a horseshoe-shaped primordium. Bilateral cardiac tubes fuse in the midline, and the fused cardiac tube undergoes further S-shaped bending. The heart increases in size, and several chambers (two atria and two ventricles) and the conducting system are formed.
Keywords: Cardiovascular System; Kardiovaskularni sistem; Embryology; Srce; Growth And Development; Biološke ure; Heart; Splanhnični obtok; rast; Mesoderm; razvoj; Splanchnic Circulation; Biological Clocks; embriologija; Mezoderm